Association of four‐factor prothrombin complex concentrate with subsequent plasma transfusion: A retrospective cohort study. Issue 1 (27th September 2020) - Roberts, Sammie J.; Pokrandt, Paul; Jewell, Elizabeth; Engoren, Milo; Berg, Mary P.; Maile, Michael D.
Abstract: Objective: To assess whether patients prescribed four‐factor prothrombin complex concentrate (4FPC) received less plasma during the following 24‐hour period than those treated for the same indications who received only plasma. Introduction: It is unclear whether 4FPC is associated with a reduction in subsequent plasma transfusion. This is important for minimising transfusion‐associated risks and for inventory management. Materials and Methods: We retrospectively studied patients treated for bleeding or coagulopathy. Individuals receiving 4FPC were matched by indication to patients treated with only plasma. Blood products received during 24‐hour follow up were compared between 4FPC and plasma‐only patients. Results: There was no difference in the number of patients receiving additional plasma (19 (21%) 4FPC patients vs 31 (34%) plasma‐only patients, P = .07) nor in the median number of additional plasma units received (0 units for both groups, interquartile range [0, 0] for 4FPC patients vs [0, 1] for plasma‐only patients, P = .09). Subgroup analysis comparing patients who received 4FPC for on‐label vs off‐label indications found no difference in the number of patients receiving plasma nor in the median number of plasma units received. Conclusion: 4FPC was prescribed to a diverse set of patients, and administration was not associated with reduced plasma transfusion at our institution.